2015
DOI: 10.1182/blood.v126.23.4586.4586
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Inflammatory Environment Is Associated with Products of the Eicosanoid Synthesis Pathways

Abstract: Background: Sickle cell disease (SCD) is a group of inherited anemia characterized by heterogeneous clinical outcome, including hemolysis, chronic inflammation, and vaso-occlusive/painful crisis. Aims: We evaluated inflammatory and anti-inflammatory mediators, such as TNFα, IL-10, IL-12, IL-1β, IL-6, and IL-8, TGF-beta, tissue inhibitor of metalloproteinase (TIMP1), matrix metalloproteinase 9 (MMP9), heme, and leukotriene B4 (LTB4), and prostaglandin E2 (PGE2), the last two are products of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In their previous study, Carvalho et al 9 found that steady-state SCD patients had the highest values of LTB4, PGE2, TIMP1, MMP9, IL-8, and IL-12 concentration compared with SCA patients in crisis and healthy control groups (p < 0.0001).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In their previous study, Carvalho et al 9 found that steady-state SCD patients had the highest values of LTB4, PGE2, TIMP1, MMP9, IL-8, and IL-12 concentration compared with SCA patients in crisis and healthy control groups (p < 0.0001).…”
Section: Discussionmentioning
confidence: 89%
“…1 Our study showed that, patients with vaso-occlusive crises (VOC) > 5/year had signi cantly higher levels of MMP-9 than those with VOC ≤ 5 /year. Carvalho et al 9 assessed 129 SCD steady-state patients (SP), 23 SCD in crisis patients (CP), and 67 healthy individuals (HC) age-and sex-matched with patients groups. They found that Steady-state SCD patients had the highest values of MMP9 concentration compared with CP and HC groups (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%